PERSONAL EMPATHY OF CLONES AND AIS: A HUMANISTIC APPROACH TO KAZUO ISHIGURO’S NEVER LET ME GO AND KLARA AND THE SUN - Jossy. J, Bibin; Dunston, G.M. Joseph (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Empathy is the ability to recognise a person or object's posture, position, and feelings as one's own. People's involuntary projection or personal empathy into for an object or for a person is a great concern of humanity that must be addressed for the overall well-being of human existence in the modern world. People are enticed to embrace refined lifestyles with ultra-modern amenities as scientific and technical advances take centre-stage in this global village. In human life, it creates loneliness, distraction, barrenness, and alienation. In Never Let Me Go and Klara and the Sun, Kazuo Ishiguro's protagonists Kathy (the clone) and Klara (the artificial intelligence) respectively feel personal empathy for their fellow humans. They are considered to be objects, capable of replacing decayed organs and broken relationships. Through a humanistic lens, this study compares human beings with mortal clones and chipped AIs, attempting to argue that they are generous enough to possess greater humane traits than human beings in realising the value of life on Earth. Following the theoretical approach of humanity and the intellectual intuition of aesthetics, Hailsham's Kathy and Jossie's artificial friend Klara offer everything they own, even their lives, to their strange human companions. In this way, the article sums up how digital advancements must improve human beings' sympathetic approach by clinging on to life values while hoping for the best in the future. Through his skillful narrative, Ishiguro wonderfully depicts the sense of empathy for the harmonious tomorrow.